Chlorine initiated photooxidation of (CH3)3CC(O)H in the presence of NO2 and photolysis at 254 nm. Synthesis and thermal stability of (CH3)3CC(O)OONO2 - Henao Arboleda, Diana Patricia (2015)
Photooxidation of (CH3)3CCHO in the presence of NO2 leads to the formation of CO, CO2, (CH3)3CC(O)OONO2 (DMPPN), and (CH3)3CONO2. The synthesis of DMPPN and thermal decomposition studies were carried out. Pressure dependence was studied at 293 K from 6.0 to 1000 mbar. Kinetic parameters for DMPPN were determined between 293 and 308 K, at total pressures of 9.0 and 1000 mbar. The values found for the activation energy and pre-exponential factor were (109 ± 3) kJ/mol, 1.7 × 1015 s-1, and (117 ± 3) kJ/mol, 5.2 × 1016 s-1 at these pressures, respectively. Thermal stability for DMPPN is similar to peroxyacyl nitrates already identified in the atmosphere, such as peroxyacetyl and peroxypropionyl nitrates. The quantum yield for photolysis at 254 nm of (CH3)3CCHO was determined to be 0.60 ± 0.05.